Perancangan Sistem Informasi Pembayaran Online pada Semester Antara Fakultas Ilmu Komputer Universitas Brawijaya - Kartika Hayunda Sari; Widhy Hayuhardhika Nugraha Putra; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Semester Antara is a intermediate semester that is held on the sidelines of even and odd semesters in each academic. Semester Antara can be used to improve grades or can take courses the next semester so that lectures become faster than Semester should be. Semester Antara registration at the Faculty of Computer Science are still manual by making payments to bank tellers and then providing proof of payment to the academic department. Registration of Semester Antara can easier when the system integrated with Midtrans. With the system, Students will be able to make payment directly by systems, and no longer went to bank nor ATM. This integration also useful to the faculty that doesn't need to cooperate with a variety of the bank, with payment gateway would connect between bank and the services provided by the faculty. To build this information system it is necessary to analyze user requirements to determine functional requirements, as well as non-functional requirements. There is system design using Object Oriented Analysis Design (OOAD). We evaluate the system design with traceability matrix, and correctness. Traceability matrix verify relation of use case, activity diagram, sequence diagram, and user interface design. The result of evaluation, there was compatibility between the needs of system and the function of system.